Perjalanan Demokrasi di Indonesia serta Pendidikan Kewarganegaraan sebagai Pendidikan Demokrasi yang Berkarakter - Tsani Shofiah Nurazizah; Dinie Anggraeni Dewi (Mahesa Research Center, 2021)
This article examines the journey of democracy in Indonesia and citizenship education as a character education for democracy. This research was conducted using the literature study method by collecting information from various sources, such as books, journals and articles related to the research discussed. The results show that the Indonesian state has implemented its democracy and experienced several periods, until now it has undergone a period of reform. One proof of the success of democracy in Indonesia is that the Indonesian people are aware of political life and have begun to voice their aspirations and opinions. To carry out democracy even better, the Indonesian nation needs to be taught democracy education through citizenship education so that the Indonesian nation has good character as citizens.